Identifikasi Jenis dan Analisis Hubungan Karakteristik Lingkungan Terhadap Kelimpahan Relatif Belangkas di Pantai Tanjung Bay Kabupaten Bangka Tengah - Vratiwi, Ayu tiwi; Pratiwi, Fika Dewi; Aisyah, Siti (Akuatik: Jurnal Sumberdaya Perairan, 2024)
Belangkas in Indonesian is called mimi which is one of the living fossils than exists today. Studies on belangkas in Indonesia are very rarely carried out and the status of the population is not yet clearly known. Considering that the gourd has very important role in nature and is a protected animal based Minister of Environment and Forestry Regulation number 2 of 2018. The research aims to examines the indentification of types and analysis of the relationship between environmental characteristics and the abundance of the gourd at Tanjung Bay Beach, Central Bangka Regency. Sampling was carried out in July- August 2023 at Tanjung Bay Beach using bottom gillnets. Environmental parameter measurements include temperature, salinity, pH, DO, brightness, current speed and substrate. The results of the research concluded that there were two species of prawns found on Tanjung Bay Beach, Tachypleus gigas and Carcinoscorpius rotundicauda. The relative abundance of prawns in Tanjung Bay, Central Bangka at station 1 is 50% of the Tachypleus gigas species and 50% of the Carcinoscorpius rotundicauda species. Station 2 is 75% Tachypleus gigas species and 25 % Carcinoscorpius rotundicauda species. Station 3 is 47,61 % Tachypleus gigas species and 52,38% Carcinoscorpius rotundicauda species. The relationship between environmental characteristics and the abundance of belangkas at Tanjung Bay Beach is strongly correlated with the parameters DO,PH, current speed, and brightness